Examining the stability derivatives of a compound helicopter. (20th October 2016) - Ferguson, K.; Thomson, D.
ABSTRACT: Some helicopter manufacturers are exploring the compound helicopter design as it could potentially satisfy the new emerging requirements placed on the next generation of rotorcraft. It is well understood that the main benefit of the compound helicopter is its ability to reach speeds that significantly surpass the conventional helicopter. However, it is possible that the introduction of compounding may lead to a vehicle with significantly different flight characteristics when compared to a conventional helicopter. One method to examine the flight dynamics of an aircraft is to create a linearised mathematical model of the aircraft and to investigate the stability derivatives of the vehicle. The aim of this paper is to examine the stability derivatives of a compound helicopter through a comparison with a conventional helicopter. By taking this approach, some stability, handling qualities and design issues associated with the compound helicopter can be identified. The paper features a conventional helicopter and a compound helicopter. The conventional helicopter is a standard design, featuring a main rotor and a tail-rotor. The compound helicopter configuration features both lift and thrust compounding. The wing offloads the main rotor at high speeds, whereas two propellers provide additional propulsive thrust as well as yaw control. The results highlight that the bare airframe compound helicopter would require a larger tailplane surface to ensure acceptable longitudinal handling qualities in forward flight. In addition, without increasing the size of the bare airframe compound helicopter's vertical fin, the Dutch roll mode satisfies the ADS-33 level 1 handling qualities category for the majority of the flight envelope.